BIOECOLOGICAL CHARACTERISTICS OF SELECTED MEDICINAL PLANTS OF THE ASTERACEAE FAMILY IN THE KUGITANG FLORA (Multidisciplinary Journal of Science and Technology, 2026)
This article examines the bioecological characteristics of selected medicinal plants belonging to the Asteraceae family in the flora of the Kugitang region. The study analyzes their distribution range, adaptation to environmental factors, phenological development stages, and pharmacological significance. The findings indicate that the Kugitang region is rich in biodiversity, and its medicinal plants play an important role in both traditional medicine and modern pharmacology. Issues related to the conservation and sustainable use of these plant resources are also discussed.